The cycle of Atahualpa's death: From the popular festival to theatrical performance - Oleszkiewicz, Malgorzata (1992)
The trauma of the Spanish conquest has penetrated deep into the memory of the American indigenous peoples, leaving deep traces in their conscience. One of the ways in which this memory is expressed and renewed is the constant repetition of the tragedy through dances and theatrical performances in different parts of America. In this study I examine one of the most significant examples of spectacles of the events of the conquest: the cycle of Atahualpa's death.